Designing Joyful and Meaningful New School Mathematics Using Indonesian Realistic Mathematics Education - Zulkardi Zulkardi (SEAMEO Regional Centre for QITEP in Mathematics, 2013)
A new issue in education in Indonesia is the change of curriculum in 2013. This paper presents what are the changes in content, media, method, and evaluation of mathematics subject at the school levels. As informed by the minister of education and culture in the national newspaper, the changes in the primary school mathematics will connect and integrate with science. This might increase the understanding of students in both the concept of mathematics and the application of mathematics in their daily lives that is also related to science. Hence, mathematics teachers need a way to design meaningful learning materials to integrate the two subjects. It is called thematic-integrated approach or one intertwined among strands or subjects. This article will discuss these both approaches. The former is mentioned in the new curriculum while the latter is one of five characteristics of Indonesian Realistic Mathematics Education (PMRI). Then the current development of PMRI after 12 years of implementation and dissemination in Indonesia will be discussed. During this discussion it will reveal how to design and implement joyful and meaningful mathematics learning materials by using the Indonesia context or culture.